Adoption of Membership Level for Critical Activities In Knowledge Chain Model Building An Investigation Analytical Study Depending on Fuzzy Logic Architecture for Organizations Pushed by Knowledge - المعاضيدي معن وعد الله; ابراهيم منال عبد الجبار (Journal of Economics and Administrative Sciences, 2016)
Abstract The aim of this research is to concentrate on the of knowledge management activities, initial activities: (Acquisition, Selection, Generation, Assimilation, Emission) knowledge, and support activities: (Measurement, Control, Coordination, Leadership) that is manipulate and controlling in achieving knowledge management cases in organization, that’s is leads to knowledge chain model, then determining the level of membership for these activities to knowledge chain model in a sample of Iraqi organization pushed by knowledge (Universities). The research depends on check list for gaining the data required, theses check list designed by apparently in diagnosing research dimensions and measurement mechanism. In the field domain, the researchers adopted the Fuzzy Logic architecture in checking the initial and support activities and its membership. The researchers concluded that the determining the level of membership function for these activities for building the knowledge chain model in Mosul and Mustansiriyah universities. The researchers suggests to all Iraqi Managements and the management in pushed by knowledge organization about the necessity of perception of gap between (Theoretical- Field) domains in appliance the knowledge management by movement to dependence the program and modern quantitative methods in explanation the theoretical reality.